Wine Landscapes by the Late Middle Ages. The Case of Jerez de la Frontera (Edad Media. Revista de Historia, 2019)
This article seeks to analyze the wine landscapes of Jerez de la Frontera by the late Middle Ages. The interaction between society and environment is discussed, with a focus on the management of natural resources in vineyards and the ploughing of riparian zones.
Keywords: Wine landscapes; Jerez de la Frontera; Fifteenth century; Environment